Ekologi Politik Pencemaran Air: Hegemoni Industri Ekstraktif dan Marginalisasi Petani di Bojonegoro - Ahmad Sholikin (Universitas Islam Darul Ulum Lamongan, 2018)
The massive expansion of the oil and gas extractive industry in Bojonegoro Regency, Indonesia, has triggered severe hydrological disruptions, jeopardizing the socio-ecological foundation of local agrarian communities. While previous studies have predominantly focused on land conflicts and revenue-sharing dynamics, this research shifts the analytical paradigm toward hydropolitics. This study aims to unpack the political ecology of water pollution, corporate hegemony, and the systemic marginalization of local farmers in the region. Employing a critical qualitative approach through an instrumental case study method, data were gathered via in-depth interviews, participant observation, and document analysis in the